Answer:
y = 3 - x + x²
Step-by-step explanation:
Given the data:
x. y
-5 33
-2 9
-1 5
0 3
3 9
4 15
6 33
General formof a quadratic model:
y = A + Bx + Cx²
Using the quadratic regression model solver for the data Given:
The quadratic model fit obtained is :
y = 3 - x + x²
Y = xe^x
dy/dx(e^x x)=>use the product rule, d/dx(u v) = v*(du)/(dx)+u*(dv)/(dx), where u = e^x and v = x:
= e^x (d/dx(x))+x (d/dx(e^x))
y' = e^x x+ e^x
y'(0) = 1 => slope of the tangent
slope of the normal = -1
y - 0 = -1(x - 0)
y = -x => normal at origin
Answer:
it relates to it for a shape
Step-by-step explanation:
It is simplified as much as it can go.
Answer: For the first one its J
The second one its H
Step-by-step explanation: